Computer, communication, and networking systems : an integrated perspective : proceedings of the International Conference on Information Engineering--ICIE'91, Singapore, 2-5 December 1991 - International Conference on Information (1991 : Singapore); Subramanian, K. R.; Seumahu, E. S. (Amsterdam ; New York : Elsevier ; New York : Distributors for the U.S., Elsevier Science Pub. Co., 1992)
Includes bibliographical references and index.